Entrepreneurs' competency, marketing innovation, and enterprise growth: uncovering the mediating role of marketing innovation - Amare Abawa Esubalew; Sunday Abayomi Adebisi (Future Business Journal)
Abstract Despite their large numbers, the vertical growth of micro, small, and medium enterprises (MSMEs) is not readily apparent, even though they have a substantial impact on Ethiopia’s economy. Earlier studies have underscored enterprise-related factors as hindrances to the expansion of MSMEs. However, entrepreneurs are blamed for their limited practice of innovative marketing that the researchers wanted to verify whether marketing innovation can positively influence the growth of MSMEs in Ethiopia. Therefore, the major objective of the study was to examine the effect of competency and marketing innovation on the growth of MSMEs in the Ethiopian business environment taking marketing innovation as a mediating variable. To collect data, researchers used a stratified random sampling technique and obtained data from 288 owner–managers of micro, small, and medium enterprises. The results of the study revealed that competency has a significant direct effect on enterprise growth. However, the study also found that the effect of competency on innovation and the effect of innovation on enterprise growth were not statistically significant. These findings suggest that competency directly influences the growth of enterprises, while the impact of innovation on growth is not evident in the context of Ethiopian enterprises. The negligible impact of competency on marketing innovation, coupled with the minimal effect of marketing innovation itself, suggests that entrepreneurs may not be prioritizing the adoption of innovative marketing strategies, assuming they can sell their existing products. However, such an approach is typically short-sighted and could leave the business exposed to future vulnerabilities. This study adds to the body of knowledge by indicating that marketing innovation does not mediate between competency and the growth of MSMEs. Instead, it is the competency of entrepreneurs that has a direct and exclusive impact on growth.